1986
DOI: 10.1016/0165-1765(86)90124-2
|View full text |Cite
|
Sign up to set email alerts
|

Minimal and maximal product differentiation in Hotelling's duopoly

Abstract: model of duopolistic competition ts re-examined. A family of utility functions is used which has as a special case Hotelling's original utility function. In a two-stage location-price game it is shown that an equilibrium exists when the curvature of the utility functions in the space of characteristics is sufficiently high. The (subgame-perfect) equilibrium never exhibits minimum product differentiation.On the other hand, not all equilibria are at maximal product differentiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
129
2
2

Year Published

1992
1992
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(140 citation statements)
references
References 6 publications
5
129
2
2
Order By: Relevance
“…The closest locations for which this equilibrium exists are, therefore, x 1 = l/4, x 2 = 3l/4. Comparing our results with those of GT, the equilibrium region in our case is smaller 5 . Price competition increases under concave costs, and firms separate more to avoid a price war.…”
Section: Horizontal Differentiationsupporting
confidence: 62%
See 1 more Smart Citation
“…The closest locations for which this equilibrium exists are, therefore, x 1 = l/4, x 2 = 3l/4. Comparing our results with those of GT, the equilibrium region in our case is smaller 5 . Price competition increases under concave costs, and firms separate more to avoid a price war.…”
Section: Horizontal Differentiationsupporting
confidence: 62%
“…An example of stores and consumers' locations TRANSPORTATION COSTS 1 The literature on product differentiation started with Hotelling (1929) and it is vast, nowadays. For example, D'Aspremont et al (1979), Economides (1986), Gabszewicz and Thisse (1986) or Anderson (1988) , among others, have analyzed the existence of the sequential first-locate-then-price equilibrium in the linear model of product differentiation under alternative convex specifications of the transportation cost function.…”
Section: Introductionmentioning
confidence: 99%
“…7 We obtain similar results under linear-quadratic transport cost (see Gabszewicz and Thisse, 1986) or under a more general family of convex transportation costs given by t(d) = td α , where d denotes distance and 1 < α ≤ 2 (see Economides, 1986 andAnderson et al, 1992, chapter 6). In Appendix 1, we generalize our results by allowing any convex transportation cost function.…”
Section: Introductionsupporting
confidence: 49%
“…0 where x is the distance between firm and consumer. Then, Economides (1986) using the family of transportation cost a functions C(x) 5 x ,1 , a , 2, showed that the region of existence of equilibrium is enlarged with the convexity of the consumers' utility function (price plus travel cost). Afterwards, Gabszewicz and Thisse (1986) showed that the combination of linear and quadratic terms in a convex transportation cost function, i.e., C(x) 5 2 ax 1 bx , a .…”
Section: Introductionmentioning
confidence: 99%